2016
DOI: 10.1002/14651858.cd008382.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Very early discharge versus early discharge versus non-early discharge in children with cancer and febrile neutropenia

Abstract: (2016). Very early discharge versus early discharge versus non-early discharge in children with cancer and febrile neutropenia. Cochrane database of systematic reviews (Online), (2), [008382].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 27 publications
0
17
0
1
Order By: Relevance
“…Several study groups advise that patients should remain hospitalized between courses, especially during induction therapy. Although patients may often be too sick to leave the hospital, several previous studies did not show a benefit of mandatory hospitalization in reducing infections, or adverse effects of early discharge after febrile episodes (Sung et al , ; Loeffen et al , ). Moreover, the risk of nosocomial infections, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Several study groups advise that patients should remain hospitalized between courses, especially during induction therapy. Although patients may often be too sick to leave the hospital, several previous studies did not show a benefit of mandatory hospitalization in reducing infections, or adverse effects of early discharge after febrile episodes (Sung et al , ; Loeffen et al , ). Moreover, the risk of nosocomial infections, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The 2012 guidelines advised using one of six different published clinical decision rules to stratify for this risk . But there are very limited data in children to enhance the safe use of risk‐adapted strategies . It has recently been shown that this absence of validity may be related to significant methodological biases during the derivation of these decision rules .…”
Section: Discussionmentioning
confidence: 99%
“…18 But there are very limited data in children to enhance the safe use of risk-adapted strategies. 25 It has recently been shown that this absence of validity may be related to significant methodological biases during the derivation of these decision rules. 26,27 Therefore, the development of new clinical decision rules, derived and validated according to rigorous methodological standards, is needed, 28,29 with consensual definitions between centers.…”
Section: Discussionmentioning
confidence: 99%
“…11 Neutropenia occurs frequently in patients receiving cancer care and is caused by cytotoxic therapy or malignant neoplasms affecting the bone marrow. 11,12 Because the presence of neutrophils was found to be important for the skin manifestation of a brown recluse spider bite, 9,10 we reviewed the symptomatology of such bites among patients, including those with neutropenia, who were cared for at St. Jude Children’s Research Hospital (St. Jude). Here, we describe the characteristics and severity of local and systemic signs of loxoscelism and evaluate the severity of the disease in patients with and without neutropenia.…”
Section: Introductionmentioning
confidence: 99%